Analisis Pengaruh Kualitas Produk terhadap Kepuasan Pelanggan Toko Fashion Mayoutfit Cabang Bandung, Indonesia - Syifa Nur Febriani (Asosiasi Ahli Administrasi Indonesia, 2023)
The purpose of this study is to determine the effect of product quality on customer satisfaction Mayoutfit Fashion Store Bandung Branch. Respondents in this study were consumers who had purchased Mayoutfit products at the Bandung branch at least once. The method used for this research is a descriptive quantitative method. The data processing is in the form of validity and reliability tests, normality tests, linearity tests and data analysis using simple linear regression assisted by SPSS v.27 software. The sample in this study were 102 respondents. The data collection is done by distributing questionnaires to respondents who meet the criteria. The results showed that product quality had a positive effect of 39.1% on customer satisfaction Mayoutfit Bandung Branch.